THE EFFECT OF APPLYING THE “FLIPPED CLASSROOM” STRATEGY ON THE ACHIEVEMENT OF PHYSICS AND SYSTEMIC THINKING AMONG FIRST-YEAR MIDDLE SCHOOL STUDENTS - Hassan Arif Abdal (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
The research aims to identify the effect of applying the “Flipped Classroom” strategy on the achievement of physics and systemic thinking among first-year middle school students. The researcher chose an experimental design with partial control. The research sample consisted of 62 first-year middle school students at Al-Warkaa Secondary School affiliated with the General Directorate of Education in Baghdad / First Al-Rusafa. The experiment sample was distributed into two groups, the first experimental, who studied according to the flipped classroom strategy, and the second, control, who studied according to the usual method. The researcher made sure of the equality of the research groups in the variables of chronological age in months, IQ, previous achievement, and systemic thinking scale. The researcher prepared a multiple-choice test and applied it to both research groups. He adopted a measure of systemic thinking after verifying its validity and reliability. Using a t-test to determine the results, the researcher concluded that the flipped classroom strategy has an effective effect on systemic thinking for the experimental group compared to the control group. The researcher proposed a number of recommendations and proposals.